Anti‐Inflammatory, Antiallergic and COVID‐19 Main Protease (Mpro) Inhibitory Activities of Butenolides from a Marine‐Derived Fungus Aspergillus costaricaensis. Issue 12 (28th March 2022) - Uras, Ibrahim S.; Korinek, Michal; Albohy, Amgad; Abdulrazik, Basma S.; Lin, Wenhan; Ebada, Sherif S.; Konuklugil, Belma
Abstract: Amid the current COVID‐19 pandemic, the emergence of several variants in a relatively high mutation rate (twice per month) strengthened the importance of finding out a chemical entity that can be potential for developing an effective medicine. In this study, we explored ethyl acetate (EtOAc) extract of a marine‐derived fungus Aspergillus cosatricaensis afforded three butenolide derivatives, butyrolactones I, VI and V (1 –3 ), two naphtho‐ γ ‐pyrones, TMC‐256 A1 (4 ) and rubrofusarin B (5 ) and methyl p ‐hydroxyphenyl acetate (6 ). Structure identification was unambiguously determined based on exhaustive spectral analyses including 1D/2D NMR and mass spectrometry. The isolated compounds (1 –6 ) were assessed for their in vitro anti‐inflammatory, antiallergic, elastase inhibitory activities and in silico SARS‐CoV‐2 main protease (M pro ). Results exhibited that only butenolides (1 and 2 ) revealed potent activities similar to or more than reference drugs unlike butyrolactone V (3 ) suggesting them as plausible chemical entities for developing lead molecules. Abstract : Chromatographic exploration of ethyl acetate extract derived from Aspergillus cosatricaensis yielded three butenolide derivatives, butyrolactones I, VI and V (1 –3 ), two naphtho‐ γ ‐pyrones, TMC‐256 A1 (4 ) and rubrofusarin B (5 ); and methyl p ‐hydroxyphenyl acetate (6 ). Chemical structures of isolated compounds were unambiguously determined by 1D and 2D NMR spectroscopy. Among butenolides, only compounds 1 and 2 unlike 3 exhibited potent in vitro activities as anti‐inflammatory and antiallergic along with in silico SARS‐CoV‐2 main protease (M pro ) inhibitory activity.